2024
DOI: 10.1021/acs.est.3c03315
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Lithium Concentrations in Groundwater Used as Drinking Water for the Conterminous United States

Melissa A. Lombard,
Eric E. Brown,
Daniel M. Saftner
et al.

Abstract: Lithium (Li) concentrations in drinking-water supplies are not regulated in the United States; however, Li is included in the 2022 U.S. Environmental Protection Agency list of unregulated contaminants for monitoring by public water systems. Li is used pharmaceutically to treat bipolar disorder, and studies have linked its occurrence in drinking water to human-health outcomes. An extreme gradient boosting model was developed to estimate geogenic Li in drinking-water supply wells throughout the conterminous Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Due to its high mobility, , Li from anthropogenic sources can easily spread in the environment and thus has a large chance of affecting microorganisms, plants, animals, and humans in broader areas. However, the biological and metabolic effects of high Li concentrations on aquatic and terrestrial ecosystems are still not well-understood and remain to be investigated in future studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its high mobility, , Li from anthropogenic sources can easily spread in the environment and thus has a large chance of affecting microorganisms, plants, animals, and humans in broader areas. However, the biological and metabolic effects of high Li concentrations on aquatic and terrestrial ecosystems are still not well-understood and remain to be investigated in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…As an emerging and potentially toxic element, Li has been found to be widely distributed in various environmental media, including air, water, and soil. It poses potential harm to microorganisms, plants, animals, and humans when present in environmentally relevant concentrations. For example, recent research found that even environmentally relevant concentrations of Li can have significant effects on plant development (e.g., soybean) through metabolic reprogramming. , Additionally, Li has been found to reduce the growth and reproduction of zooplankton (e.g., Daphnia magna) and cause oxidative damage to invertebrates (e.g., earthworm). Furthermore, the presence of Li in drinking water can impact human health by inducing abnormalities and dysfunctions through multiple metabolic pathways. The US Environmental Protection Agency (US EPA) has proposed a provisional reference dose ( p -RfD) of 2 μg kg –1 day –1 and a health-based screening level of 10 μg/L for Li in drinking water. , To regulate the exposure to Li, the Eurasian Economic Union has established a limit of 30 μg/L for Li levels in packaged drinking water, including natural mineral water . Furthermore, there have been widespread reports on the toxicity of other associated toxic elements such as F, Rb, Cs, Zn, and Tl. , Considering their potential toxicity and health effects, it is crucial to investigate the impact of Li extraction activities on the levels of Li and associated components in the environment.…”
Section: Introductionmentioning
confidence: 99%